Exoneration clause as limitation of criminal liability in digital business in Indonesia - Rahmanu Wijaya,; Sarmini,; Oksiana Jatiningsih,; Rr. Nanik Setyowati,; Listyaningsih,; Mi'rojul Huda, (Technium Social Sciences Journal, 2023)
Digital business in Indonesia is developing very rapidly, many new business actors have emerged with various types of businesses. The development of this digital business cannot be separated from the condition of society as a market, where it is recorded that the majority of Indonesian people are active internet users. The frame of the legal relationship between business actors and the community with a position as a consumer is based on an agreement in which exoneration clauses are commonly found. Given the condition of the Indonesian people with a low level of literacy, the existence of the agreement clause is less scrutinized or not properly understood. On the other hand, many business actors are of the view that the existence of this clause has caused their position to become superior. So that it can ignore all objections raised by consumers, and even avoid criminal liability. The exoneration clause is the cause, so this legal research explores whether the exoneration clause can indeed limit digital business actors in Indonesia from criminal liability. The method used is the Statute Approach, which explores related laws and regulations. However, the depth of this research which is supported by the expertise of each researcher also reveals the Anthropological, Social, and Political sides. The results of the study show that the exoneration clause does not absolutely provide limitations on criminal liability for business actors or digital businesses.